2016
DOI: 10.1002/14651858.cd011714.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Home telemonitoring and remote feedback between clinic visits for asthma

Abstract: Current evidence does not support the widespread implementation of telemonitoring with healthcare provider feedback between asthma clinic visits. Studies have not yet proven that additional telemonitoring strategies lead to better symptom control or reduced need for oral steroids over usual asthma care, nor have they ruled out unintended harms. Investigators noted small benefits for quality of life, but these are subject to risk of bias, as the studies were unblinded. Similarly, some benefits for lung function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 101 publications
2
87
0
Order By: Relevance
“…The primary focus of most of the Android (Google, Mountain View, CA, USA) operating system asthma applications has been on patient self-monitoring and self-assessment, but there are low levels of health information quality across all applications [15]. Self-management facilitated by a healthcare professional is important for the control of symptoms and prevention of exacerbations [16]. Existing standards for conducting trials and reporting results in mHealth should be reported.…”
Section: Impact Of Mhealth In Asthma and Allergic Diseasesmentioning
confidence: 99%
“…The primary focus of most of the Android (Google, Mountain View, CA, USA) operating system asthma applications has been on patient self-monitoring and self-assessment, but there are low levels of health information quality across all applications [15]. Self-management facilitated by a healthcare professional is important for the control of symptoms and prevention of exacerbations [16]. Existing standards for conducting trials and reporting results in mHealth should be reported.…”
Section: Impact Of Mhealth In Asthma and Allergic Diseasesmentioning
confidence: 99%
“…However, the findings of individual studies have been inconsistent. Although telemonitoring (text messaging, Web systems, etc) was not associated with better control of asthma symptoms when compared with usual care [32], internet-based self-management support has been shown to improve asthma quality of life and asthma control [33].…”
Section: Introductionmentioning
confidence: 99%
“…Daily home FEV 1 telemonitoring did not reduce exacerbations in children with severe asthma (49). A recent Cochrane review found no additional benefits of telemonitoring for asthma control or exacerbations, over usual asthma care (50). Devices differ widely on their inclusion of instructive videos, graphical descriptions, and immediate feedback on the quality of the breathing maneuver (47) ( Table 1).…”
Section: Home Pft Measurementsmentioning
confidence: 99%